L’industrie des poudres et explosifs sous l’Occupation : un chantier de recherche à ouvrir - Patrice Bret (L'Atelier du CRH)
Since the turn of the 21st century, the history of French industry under German Occupation has become a very active and well-defined research field, but the Powder and Explosives sector has remained neglected by this movement, both in its public and private components. Taking stock of the historiography and institutional changes in the sector between 1939 and 1945, the article also opens up the question of Collaboration, industrial braking and Resistance through unpublished archives on political purge both in the Powder and Explosives private industry and at the Toulouse National Gunpowder Factory